Knowledge Transfer among Information and Communication Technology (ICT) firms for innovation in Malaysian Technology Parks: The Challenge of Macro Stickiness - Mhd. Sarif, Suhaimi (2012)
This paper examines the challenge of macro stickiness (MS) as moderator that influences knowledge transfer (KT) for innovation among ICT firms. The study is based on technological learning framework that argues technological learning could be hindered from its effectiveness in the presence of macro stickiness phenomena. Macro stickiness occurs from vague and inadequate guidance in the policies for innovation and economic development. The policies should incorporate critical success factors for technological learning, i.e. knowledge transfer among technological firms such as ICT firms. The study used personal interview with policy makers, ICT executives and government officers to solicit their views pertaining to pull and push factors for knowledge transfer for innovation among ICT firms. ICT firms are the participants to encourage innovation vis-à-vis KT in Malaysian Technology Parks (MTPs). However, the interview results show some concerns about the presence of MS in KT that related to government policies for innovation and respective business decisions that reduce the full potential for KT for innovation among ICT firms. The study recommends the government, industry and academics to work closely through seminars, workshop, informal gathering, and retreat to increase trust and confidence so that they could engage in KT for innovation. Nevertheless, the results of the study are not conclusive due to the sampling size and the depth of the analysis. Future studies should use case studies and personal interview with more informants.